2022
DOI: 10.2147/hiv.s393093
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Successful Intensive Adherence Counseling in Rural Northern Uganda: An Exploratory Interview with HIV-Positive Clients Using the COM-B Framework

Abstract: Intensive adherence counseling (IAC) was introduced as a strategy to enhance adherence to antiretroviral therapy (ART) among HIV clients with non-suppressed viral loads. There has been sub-optimal viral load suppression among HIV clients in Uganda enrolled in IAC. However, there is a scarcity of literature on the barriers and facilitators of successful IAC. We aim to explore the barriers and facilitators to successful IAC among HIV-positive clients seeking care in public health facilities in rural northern Uga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Quality of counseling was yet another important factor influencing adherence to second clinic visit that came up during our survey and in-depth interview. Although this finding is contrary to that reported by a study in Kenya, 26 which did not find any benefits of counselling to adherence to clinic visit among HIV clients, our finding is consistent with a study among HIV clients in Uganda 27 which found that quality counselling improves HIV linkages and management in care. The disparity between findings could be attributed to the use of lay counsellors in the Kenyan study, who may be less skilled in counselling.…”
Section: Discussionsupporting
confidence: 55%
“…Quality of counseling was yet another important factor influencing adherence to second clinic visit that came up during our survey and in-depth interview. Although this finding is contrary to that reported by a study in Kenya, 26 which did not find any benefits of counselling to adherence to clinic visit among HIV clients, our finding is consistent with a study among HIV clients in Uganda 27 which found that quality counselling improves HIV linkages and management in care. The disparity between findings could be attributed to the use of lay counsellors in the Kenyan study, who may be less skilled in counselling.…”
Section: Discussionsupporting
confidence: 55%
“…For instance, a Ugandan study found that only 23% of paediatric patients with HIV achieved viral suppression after IAC [46]; another Ugandan study evaluated the outcomes of IAC in improving viral suppression and found that 48.2% of participants with HIV achieved viral suppression following IAC [47]; and in Zimbabwe, 31.2% of participants with HIV who underwent a repeat VL after IAC achieved VL suppression [48]. This low success rate of IAC could be due to various challenges affecting the implementation of IAC, including clients missing IAC sessions, shortage of food, stigma and discrimination, delayed VL results, a lack of incentives, and heavy workloads, among others [46,49]. In our study, people living with HIV were given an incentive in the form of a transport refund every time they came to the health facility for IAC, which led to all participants in the intervention arm reporting for all their IAC sessions.…”
Section: Discussionmentioning
confidence: 99%